Determination of photovoltaic hydrogen production potential in Portugal: a techno-economic analysis - Silva, Hugo Gonçalves; Alami Merrouni, Ahmed; Touili, Samir; Neto, Jorge (Frontiers in Energy Research, 2024)
Hydrogen is expected to become a dominant energy vector in a scenario where renewable energies will prevail over other conventional sources. This suggests that beyond its conventional industrial applications, such as in the chemical industry, hydrogen is poised to find numerous additional uses, including serving as a fuel for internal combustion engines. Consequently, global demand is expected to surge significantly, necessitating the implementation of large-scale hydrogen production units from renewable sources. This is particularly pronounced in Europe, where recent energy directives have set ambitious targets in this regard. Consequently, it becomes imperative to evaluate potential locations suitable for hosting these hydrogen production facilities. In this study, particular attention is directed towards photovoltaic-fed water electrolysis as a method for hydrogen production. This choice is informed by the maturity and affordability of these technologies, coupled with the abundant solar energy resource available in Southern Europe. To this end, it is utilized 23 years of hourly meteorological data obtained from the Portuguese Meteorological Service. This dataset enables the development of typical meteorological year files for nearly 90 stations across mainland Portugal. These files were inputted into a model simulating a 120 MWp photovoltaic plant, utilizing the System Advisor Model. The electricity generated by this plant was subsequently used to simulate the hydrogen production using an in-house developed model for the electrolyser. Finally, the simulation results were used to develop the first atlas for Solar Hydrogen production capacity and cost in Portugal. The techno-economic results indicate that annual specific hydrogen production can achieve values above 30 kg/kWp, with the levelized cost of hydrogen below 4.0 €/kg, especially, in the southern regions (Alentejo and Algarve) and the central-east area (Beira Interior). This makes these regions highly attractive for hosting large-scale photovoltaic hydrogen production plants and very competitive in the hydrogen market, especially with neighbouring countries like Morocco and Spain.